SERUM URIC ACID, LEFT VENTRICULAR MASS AND CARDIOVASCULAR DEATH. THE URIC ACID RIGHT FOR HEART HEALTH (URRAH) STUDY. (June 2022) - Muiesan, Maria Lorenza; Salvetti, Massimo; Paini, Anna; Rosei, Claudia Agabiti; Virdis, Agostino; Casiglia, Edoardo; Tikhonoff, Valerie; Barbagallo, Carlo Maria; Cirillo, M; Desideri, Giovanbattista; Ferri, Claudio; Galletti, Ferruccio; et al.
Abstract : Objective: A relationship between serum uric acid(UA)and CV events has been documented in the URRAH study.The association between UA and left ventricular mass index(LVMI)has been investigated with heterogeneous results.Aim of this study was to investigate the association between UA and LVMI and whether UA and LVMI or they combination may predict the incidence of death for CV disease(CVM)in a large Italian cohort in the frame of the Working Group on Uric Acid and Cardiovascular Risk of the Italian Society of Hypertension(SIIA) Design and method: URRAH study is a nationwide, multicentre, observational cohort study involving data on subjects aged 18to95years, recruited on a community basis from all regions of Italy under the patronage of the SIIA.CVM was defined as death due to fatal myocardial infarction, stroke, sudden cardiac death, or heart failure.Multivariate Cox regression models having CVM as dependent variables, adjusted for age, sex, BMI, SBP, glycemia, total cholesterol, triglycerides, HDL-cholesterol, smoking and estimated glomerular filtration rate(eGFR)were used to search for an association between UAandLVMI as a continuous variable and CVM.LVH was defined asLVMI> 95 g/m2 in women and 115 g/m2 in men Results: 10733 subjects(mean age, 54years;51%female)with echocardiographic LVMI measurements were included in the analysis study.A significant association between UA and LVMI was confirmed in multiple regression analysis in both sexes(men:beta0, 095, F5.47, P < 0.001;women:beta0, 069, F4.36, P < 0.001).During follow-up(median 130months), 319subjects died for a CVevent, including myocardial infarction, angina pectoris, congestive heart failure and cerebrovascular disease.Previously identified sex specific cut off values(5.6 mg/dl men, 5.1 mg/dl women)and LVH were used to define 4 different groups(normal UA and LVMI, increased UA and no LVH, normal UA and LVH, increased UA and LVH).Kaplan–Meier curves showed a significantly poorer survival rate in the group with higher UA and LVMI(log-rank chi-square298.105;P < 0.0001).Multivariate Cox regression analysis showed that in women LVH alone[HR2, 25(1.076to4, 721);P = 0.03]and the combination of higher UA and LVH[HR3, 785(1.789to8.008);P = 0.001], but not hyperuricemia alone, were associated with a higher risk of CVD, while in men hyperuricemia without LVH[HR2.338(1.292to4.232);P = 0.005], LVH without hyperuricemia[HR3.008(1.750to5.449);P = 0.001]and their combination[HR5.273(3.044to9.135);P = 0.001]were all associated with a higher incidence of CVM Conclusions: Our findings demonstrate that UAis independently associated with LVMI and suggest that combination of hyperuricemia with LVH is an independent and powerful predictor for CVM both in men and women.The association between UAandCVD events may be explained in part because of a direct association of UAwithLVMI